PROTEIN GELS: A MINI REVIEW - Harikedua, Silvana Dinaintang (Sam Ratulangi University, 2019)
The use of gelatin as food additive for gelling properties was discussed in this review. Three products (i.e. gel dessert, yoghurt, and surimi) were selected as the main focus of this mini review since they characterized 3 different protein gelation system. The mechanism of gelatin gelation in water system was described by gel dessert, the gelation of casein in dairy product was presented by yoghurt, and the gelation of sarcoplasmic protein in meat system was exemplify by surimi. Overall, the mechanism of gelation mainly contributed by the networking of protein-protein which is strengthen by the intermolecular bond and intramolecular bond.